Biosynthesis of silver nanoparticles (AgNP) using leaves extract of Jatropha Curcas L. - Nury, Dennis Farina; Febriyanto, Pramahadi; Arum, Amalia Sekar; Mayastuti, Sherina; Luthfi, Muhammad Zulfikar (Konversi, 2023)
Due to the increased demand for ecologically friendly material synthesis techniques, biosynthesis of nanoparticles has drawn a lot of attention. It has been claimed that an environmentally benign method for producing silver nanoparticles (AgNPs) efficiently can be achieved utilizing leaves extract of the multifunctional plant Jatropha curcas. Maximum absorption were obtained from different types of solvents, in distilled water resulted at wavelength 428-434, meanwhile in ethanol 96% solvent, maximum absorption was obtained at wavelength 338-340 nm by using UV-Vis spectrophotometer, respectively. The results of FTIR formed on silver nanoparticles are O-H functional groups with distilled water and O-H functional groups, and C-O with 96% ethanol solvent. The particle sizes formed in distilled water and 96% ethanol solvents were 104.6 nm and 110.7 nm respectively with PI values of 0.341 and 0.644. Based on the results, (AgNPs) passes the nanoparticle range caused by agglomeration. It can be interpreted that the results of this synthesis are fine particles.